Strength ranking for interfaces between a TiN hard coating and microstructural constituents of high speed steel determined by micromechanical testing - Matthias Gsellmann; Thomas Klünsner; Christian Mitterer; Martin Krobath; Michael Wurmshuber; Harald Leitner; Werner Ecker; Stefan Marsoner; Verena Maier-Kiener; Daniel Kiener; Gerald Ressel (Materials & Design, 2021)
Knowledge about the adhesion of protective hard coatings on tool materials is of great importance to understand their failure mechanisms in metalworking. Until now, common techniques such as scratch and indentation tests are used to establish a qualitative ranking of a coating’s adhesion on various substrate materials. Nevertheless, there is a lack of quantitative measures to describe the strength of the interfaces between individual microstructural constituents of substrate-coating composites. The current work investigates the interfacial strength and thus the adhesion of TiN deposited as a hard coating on an MC-type carbide, an M6C-type carbide and on martensite being constituents of high speed steels. Tensile stresses were introduced at the interface between TiN and the individual microstructural constituents of a high speed steel via micromechanical testing of a novel MSC specimen within a scanning electron microscope. The tested MSC specimens were subsequently investigated in detail by scanning electron microscopy. Evaluation of the interface stress at fracture via finite element analysis yielded a ranking in interface strength and therefore coating adhesion in a sequence from high to low strength values from MC/TiN over M6C/TiN to martensite/TiN.